Genetic Diversity of Amaranthus dubius Mart. (Khedha) Used Tribal Place in Chhattisgarh, India - Chandravanshi, Deepika; Sharma, P. K.; Banjare, C.; Chandravanshi, Deepa (International Journal of Bio-resource and Stress Management, 2018)
In India, the leaves of a large number of wild and cultivated plants are used as vegetables. They have a very high protective food value and are very easy to grow. In Chhattisgarh, the life and economy of the tribal and local people are intimately connected with the natural vegetation. The present investigation research was conduct during Rabi Season during year 2014-15 and 2015-16 at Research and Instructional Farm, Department of Horticulture, Indira Gandhi Krishi Vishwavidyalaya, Raipur (C.G.). The experiment was comprised of twenty five genotypes and check variety CO-1 of Amaranthus dubius Mart. (Khedha) laid out in Randomized Block Design (RBD) with three replications. The information was based on an ethno-botanical field study of the different parts of Chhattisgarh. Morphological characters recorded in all the genotypes as per the minimal descriptors for leafy vegetables presented in table no. 1. The plant height varies from 5 m to 10 m among various species. Leaves are oblong to elliptical with color ranged from light to dark green with some expressing red pigment throughout the genus. The inflorescence is very prominent, colorful, terminal and contain one male flower per glomerule. The obtained data expressed maximum fibre content in variety of CO-1 (15.67%) followed by genotype IGKB-2014-51 (15.50%) and IGKB-2014-53 (15.13%) was observed. Variety CO-1 and genotype IGKB-2014-51 are statically at par with each other.